Peran Televisi Kampus BTV Sebagai Media Informasi Dan Publikasi Kegiatan Kampus Melalui Program Magang Mahasiswa - Muhammad Fathur Rahman; Dimas Umboro (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
The development of communication and information technology has encouraged universities to utilize campus media as a means of disseminating information and publishing academic and non-academic activities. Bina Darma TV (BTV) is a campus television station that plays a role in conveying information, documenting activities, and building a positive image of Bina Darma University. This study aims to determine the role of BTV as a medium for information and publication of campus activities through the student internship program. The results indicate that BTV plays a significant role in disseminating campus information and serving as a means of developing student competencies in the fields of communication and broadcasting.